China e-commerce legislation: adjusting foreign experience of legal regulation - Miashchanava, Maryia V. (Journal of the Belarusian State University. Law, 2021)
The models of legal regulation of e-commerce in foreign countries are analysed. Attention is focused on the need to improve of the legislation of the Republic of Belarus in the field under the study, including regulation of the activities of e-commerce platforms. The phenomenon of market monopolisation by gatekeepers is considered, the negative consequences of this phenomenon for the national economy, including the possibility of the formation and subsequent increase of the digital divide, are pointed out. The e‑commerce law of the People’s Republic of China is analysed from the point of view of acceptable control mechanisms over the activities of e‑commerce operators, including platform operators, protection of consumers involved in transactions on marketplaces, antitrust regulation and protection of intellectual property rights. A number of terms, used in the field of electronic commerce, are proposed for their possible implementation in the legislation of the Republic of Belarus.
Keywords: digital ecosystem; e-commerce platform; marketplace; e-commerce operator; gatekeepers